Barriers and limitations to the development of a telemental health service for workers in Peru- A user-centered approach - Astete-Cornejo, J.; Cruz-Ausejo, L.; Cainamarks Alejandro, J.; Burgos-Flores, M.A.; Ambrosio-Melgarejo, J.; Rosales-Rimache, J.; Cruz, S.G. (Public Library of Science, 2025)
Introduction Over the past decade, the surge in digital healthcare services has transformed traditional healthcare, requiring multidisciplinary engagement to adapt to the digital realm. The rise of telehealth services, particularly amid COVID-19, has been widely embraced globally, but its implementation in Peru faces unique challenges, including infrastructure issues and economic constraints. Therefore, this research aims to identify the barriers and limitations in developing a telemental health service for screening, evaluation, and timely referral of vulnerable occupational groups. Materials and methods A qualitative study was undertaken. We adopted a phenomenological approach, utilizing semi-structured interviews with vulnerable occupational groups and decision-makers. We conducted 23 interviews: 5 providers of telemental health services, 5 teachers users, 5 police officers users and 5 health professionals of telemental health services, and 3 decision-makers involved in telemental health regulation in Peru.; exploring experiences, barriers, and facilitators related to mental telemental health. The interviews were recorded and transcribed verbatim, furthermore, a thematic analysis was done to identify key themes. Results The research identified barriers and limitations to developing a telemental health services screening service based on the experiences of workers, some of them were related to user dissatisfaction, emphasizing the need for personalized solutions beyond technical aspects. Scheduling issues call for flexibility and improved communication. Healthcare professionals’ varied experiences highlight the necessity for targeted training, while successful telemental health services integration demands addressing resource limitations through a comprehensive approach. Conclusion The study advocates for a holistic, user-centred paradigm in telemental health services implementation, addressing both technological aspects and human and systemic elements. Multifaceted challenges inherent in telemental health, particularly in Peru, emphasize the need for strategic interventions by stakeholders. The study calls for a policy shift towards enhancing telemental health equity through system-level changes and eliminating structural barriers for marginalized populations.
Keywords: Thematic analysis; Telemedicine; Telehealth; Health care; Digital health; Mental health; Nursing; Service provider; Medicine; Service (business); Qualitative research; Business; Political science; Sociology; https://purl.org/pe-repo/ocde/ford#3.02.27